Lumbar Intraspinal Calcium Pyrophosphate Deposition: A Comprehensive Case Study - Juan M. López-Navarro; Diego A. Sandoval-Lopez; Pavle Popovic; Vasileios Karantzoulis; Zeid Bittar; Edgar Santos; Farzam Vazifehdan (Journal of Central Nervous System Disease)
Introduction Calcium pyrophosphate deposition (CPPD) disease is characterized by calcium pyrophosphate crystals in hyaline and fibrocartilage. Chondrocalcinosis, a radiographic hallmark for CPPD, becomes more prevalent with age. Although CPPD mainly targets peripheral joints, spinal involvement, affecting intervertebral discs and spinal ligaments, is less common but significant, seen in 24.3% of hospitalized patients with CPPD disease. This report describes a rare case of spinal CPPD causing spinal canal stenosis in the lumbar region. Case Description A 79-year-old woman with a 3-year history of low back pain presented with severe left-sided pain and mobility impairment. Initial examination showed lumbar tenderness and normal muscle strength. Computed tomography (CT) and magnetic resonance imaging scans revealed a calcified extradural mass occupying the anterior portion of the lumbar spinal canal, most likely associated with the posterior longitudinal ligament. The patient underwent L3-L5 hemilaminectomies and dorsal spondylodesis, removing a whitish intraspinal mass. Histopathology confirmed CPPD. Post-surgery, the patient experienced initial pain relief but required emergency surgery due to complications. Over the next year, her mobility and pain improved significantly. Discussion Spinal CPPD manifests with varied clinical presentations, complicating diagnosis. Imaging reveals calcifications ranging from deposits to mass-like lesions causing compression. CT provides detailed visualization of characteristic calcifications, aiding in diagnosis, while histopathology remains the gold standard. Multidisciplinary collaboration is vital for accurate diagnosis and optimal management.